Mechanochemistry: an efficient and versatile toolbox for synthesis, transformation, and functionalization of porous metal-organic frameworks - Stolar, Tomislav; U arevi, Krunoslav (CrystEngComm, 2020)
Mechanochemistry is nowadays recognized as a green approach to chemical synthesis, but the full scope of the accompanying solid-state reactivity is just beginning to be unravelled. This is especially true for the preparation of porous metal-organic frameworks, whose synthesis by the use of mechanical force lagged behind that of other relevant classes of materials. Nevertheless, mechanochemical procedures have rapidly evolved from a mere synthetic curiosity towards efficient methods for obtaining high-quality MOFs on different scales. This Highlight is dedicated to the functional approach of using mechanochemistry for the preparation of catalytically active MOF composites and mixed-metal and mixed-ligand MOFs with synergistic properties as well as fine-tuning of the MOF performance via defect engineering and amorphization. Multiple ways in which the synergy of mechanochemistry and MOFs advances the field of materials chemistry are presented here.